2017
DOI: 10.1080/10903127.2017.1308611
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Airway Type and Its Association with Chest Compression Interruptions During Out-of-Hospital Cardiac Arrest Resuscitation Attempts

Abstract: While summary measures of chest compression delivery did not differ significantly between airway classes in this observational study, repeated attempts following failed initial DL during cardiopulmonary resuscitation were associated with an increase in the number of pauses in chest compression delivery observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 41 publications
0
21
1
1
Order By: Relevance
“…However, repeated attempts after failed initial DL (but not VL) during CPR were associated with an increase in the number of pauses in chest compression delivery. 56 Ongoing clinical trials may provide more insight into the optimal airway management during cardiac arrests in the out-of-hospital setting (clinicaltrials.gov identifiers NCT02419573 and NCT02327026, and isrctn.com identifier ISRCTN08256118).…”
Section: Discussionmentioning
confidence: 99%
“…However, repeated attempts after failed initial DL (but not VL) during CPR were associated with an increase in the number of pauses in chest compression delivery. 56 Ongoing clinical trials may provide more insight into the optimal airway management during cardiac arrests in the out-of-hospital setting (clinicaltrials.gov identifiers NCT02419573 and NCT02327026, and isrctn.com identifier ISRCTN08256118).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Wang et al found that ETI performance was associated with chest compression interruptions, and that the no-flow time was actually extended in situations where CPR was required. 19 Jarman et al 20 reported no differences in CPR interruption time according to the prehospital airway management method, and showed that the failure of the first ETI attempt via direct laryngoscopy actually increased the duration of interrupted chest compressions. Therefore, we must consider the possibility that interrupted chest compressions do not differ according to the airway management method and may actually increase for subjects who undergo advanced airway management; this would explain why advanced management did not affect the neurologic outcomes in real-world situations.…”
Section: Discussionmentioning
confidence: 99%
“…In one study of experienced clinicians, VL was associated with significantly fewer episodes of prolonged (> 10 s) interruptions in chest compressions; the intubation success rate was not significantly different [ 26 ]. In a further study, VL use was associated with shorter pauses in compressions compared with direct laryngoscopy when initial tracheal intubation was not successful [ 27 ].…”
Section: Airway and Ventilation Techniques During Cprmentioning
confidence: 99%
“…In an observational study of 100 pre-hospital intubations by paramedics, tracheal intubation attempts during CPR caused a median 110 s (IQR 54–198 s) of interruption, and in a quarter of cases the interruptions were over 3 minutes [ 19 ]. More recent OHCA observational data (339 patients) suggest duration of the longest pauses, number of pauses over 10 s and chest compression fraction (proportion of time compressions being given) may be similar with bag-mask, SGA and tracheal intubation [ 27 ]. In addition, data from 2767 cases of OHCA suggest the chest compression fraction is only slightly less with a tracheal tube (72.4 vs 76.7%) [ 34 ].…”
Section: Comparisons Between Airway Techniques During Cprmentioning
confidence: 99%